2017
DOI: 10.3389/fmars.2017.00061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans

Abstract: Amoebic gill disease (AGD) caused by Neoparamoeba perurans, has emerged in Europe as a significant problem for the Atlantic salmon farming industry. Gross gill score is the most widely used and practical method for determining AGD severity on farms and informing management decisions on disease mitigation strategies. As molecular diagnosis of AGD remains a high priority for much of the international salmon farming industry, there is a need to evaluate the suitability of currently available molecular assays in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…DNA was extracted from swabs using the Wizard® Genomic DNA Purification Kit (Promega) as per the manufacturer's protocol. Real‐time quantitative PCR targeting the 18S rRNA gene of N. perurans was performed on purified DNA using the methods previously described by Downes et al (). The C T values were analysed as a relative quantification to the 0 mg/L control and normalized to the endogenous control gene Elf (elongation factor) as described previously (Downes et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted from swabs using the Wizard® Genomic DNA Purification Kit (Promega) as per the manufacturer's protocol. Real‐time quantitative PCR targeting the 18S rRNA gene of N. perurans was performed on purified DNA using the methods previously described by Downes et al (). The C T values were analysed as a relative quantification to the 0 mg/L control and normalized to the endogenous control gene Elf (elongation factor) as described previously (Downes et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Following killing on day 15 post-treatment, the severity of AGD was examined using two established methods, gross gill score and quantitative PCR specific to N. perurans. The gross gill score was quanti- Elf (elongation factor) as described previously (Downes et al, 2017).…”
Section: Quantifying Agd Severitymentioning
confidence: 99%
“…Presumptive diagnosis of AGD is based on clinical signs and the microscopic observation of typical amoebae on wet gill smears. The presence of N. perurans can be confirmed using polymerase chain reaction (PCR), which does not require the destruction of the fish host (Downes et al 2017, 2018b), or destructively by histology, in which observed abnormalities are epithelial hyperplasia, lamellar fusion, inflammation, cell death, presence of interlamellar vesicles and presence of amoeba (Adams et al 2004; Mitchell & Rodger, 2011).…”
Section: Specific Types Of Marine Salmonid Gill Diseasementioning
confidence: 99%
“…The aims of this study were to assess the efficiency of the different swabs for the detection of the amoebic pathogen, N. perurans , through in vitro testing (spiking and plate swabbing) and in vivo testing of AGD‐infected Atlantic salmon, and also to determine which of the tested gill arches could potentially demonstrate a higher amoebic load during testing. Whilst previous studies have focused on comparing different PCR techniques for the development of better pathogen quantification using non‐lethal sampling methods (Bergmann & Kempter, 2011; Downes et al., 2017; Monaghan, Thompson, Adams, & Bergmann, 2015), this study focused on the type of swabbing material and location of the gill swabbing. The results showed that the swab material might not be critical for timely diagnosis of AGD, although Calgiswab ® swabs presented lower Ct values during the in vivo trials, which suggests that higher quantities of DNA were retrieved using this approach and that it could therefore offer greater sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of non‐destructive tools to confirm the presence of N. perurans was studied by Downes et al. (2017). When non‐destructive gill swabbing was performed, results showed a great improvement on the sensitivity of diagnosis in comparison with gill filament biopsies.…”
Section: Introductionmentioning
confidence: 99%